2019
DOI: 10.12998/wjcc.v7.i2.242
|View full text |Cite
|
Sign up to set email alerts
|

Collision carcinoma of squamous cell carcinoma and small cell neuroendocrine carcinoma of the larynx: A case report and review of the literature

Abstract: BACKGROUNDCollision carcinoma is rare in clinical practice, especially in the head and neck region. In this paper, we report a case of squamous cell carcinoma (SCC) and neuroendocrine carcinoma (NEC) colliding in the larynx and review 12 cases of collision carcinoma in the head and neck to further understand collision carcinoma, including its definition, diagnosis, and treatment.CASE SUMMARYA 61-year-old man presented with a 1-year history of hoarseness. Contrast-enhanced magnetic resonance imaging of the lary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Collision tumor refers to two malignant tumors coexisting and the components originate from the same area or organ but with different morphologies according to histologic examination. There are various theories related to collision tumors; however, due to low frequency and individuality, controversy still exists regarding the pathogenesis and definition (8). Reports on the synchronous and metachronous coexistence of SmCC and SCC in the same anatomic space in the head and neck are rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collision tumor refers to two malignant tumors coexisting and the components originate from the same area or organ but with different morphologies according to histologic examination. There are various theories related to collision tumors; however, due to low frequency and individuality, controversy still exists regarding the pathogenesis and definition (8). Reports on the synchronous and metachronous coexistence of SmCC and SCC in the same anatomic space in the head and neck are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of SmCC in the head and neck extend into adjacent spaces without extensive bone destruction (3). A previous study reported on SmCC of the nasal cavity with extensive and aggressive destruction of bone at the skull base and invasion of the right orbit (8).…”
Section: Discussionmentioning
confidence: 99%
“…The highest incidence is seen in developed countries. In recent years, the incidence has increased rapidly and younger patients in developing countries have been identified[ 5 ]. The most important risk factor is genetic predisposition depending on the type of mutation, in addition, red meat, alcohol, smoking and excess body fat are also risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Collision carcinomas have been described in various organs including the cranium, lungs, stomach, larynx, and thyroid gland [3][4][5][6][7] with several cases reported in the head and neck but very rarely in the oral mucosa (Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Indeed, and to the best of our knowledge, only two cases of oral collision cancer have been reported (Table 1: Cases 1 and 4). More specifically, Takeda et al 8 describe a collision between duct carcinoma and SqCC in the lip, while Falanga et al 11 report a collision cancer between desmoplastic melanoma and SqCC occurring in the mouth floor.…”
Section: Discussionmentioning
confidence: 99%